PERBANDINGAN KADAR GLUKOSA DARAH VENA PADA PASIEN SEBELUM DAN SESUDAH MENJALANI TERAPI BEKAM DI KLINIK SEHAT HARAPAN IBU - Andri Andri; Ratih Ayu Atika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Background: Cupping therapy is one of alternative therapies used to control blood glucose levels. Cupping is a minor surgical excretion procedure which uses negative pressure and is thought to cleanse the blood and interstitial spaces from harmful and toxic substances. Wet cupping has been medically proven to have beneficial effects in dealing with various diseases which have different etiologies and pathogenesis, for example diabetes mellitus. Research Purpose: This research was conducted to find out the difference in venous blood glucose levels in patients before and after undergoing cupping therapy at the Harapan Ibu Health Clinic. Research Design: This was an analytic quantitative research with cross sectional approach. The population in this study was all patients undergoing cupping therapy and meeting inclusion criteria. The total respondents were 51 patients chosen through consecutive sampling technique. Research Result: The results of the research showed that most of respondents were in 31-40 years age range, totaled 19 people (37,2%), and already finished eating before doing research, totaled 34 respondent (66,7%). The blood sugar levels before undergoing cupping therapy was in the category of 70 to 99 mg/dl, totaled 24 respondents (47.1%), and in the category of 65 to 94 mg/dl after undergoing cupping therapy, totaled 27 respondents (52.9%). The results of statistical analysis showed that there were significant differences in venous blood glucose levels before and after undergoing cupping therapy at Harapan Ibu Health Clinic (p-value = 0,000). Conclusion and Recommendation: From all the research results, it is expected to the health service institution to be able to monitor and educate the clinics which provide cupping therapy located in the District of Pidie Aceh, in order to maintain the safety and sterility of the tool before and after undergoing therapy to prevent the spread of diseases which can be transmitted through the blood.Keywords: cupping therapy, venous blood glucose level, diabetes mellitus